Rancang bangun set eksperimen kalorimeter digital dengan pengindera sensor termokopel dan load cell berbasis arduino uno (A design of experimental set with a thermocouple sensor and load cell sensing based on arduino uno) - Mardiyah Noviyanti; - Hufri (PILLAR OF PHYSICS, 2020)
A calorimeter is a device used to determine heat capacity, specific heat capacity and latent heat capacity. Calorimeter needs to be developed in terms of temperature and mass measurements into digital measurements using thermocouple sensors and Load Cell sensors and Arduino Uno as microcontrollers. This research is included in engineering research. This study describes the performance specifications and design specifications of a digital calorimeter experiment set. Performance specifications describe the system functions of the experimental set builder, while design specifications explain the accuracy and accuracy of the tools. The measurement technique is done directly and indirectly. Direct measurements are made of temperature and mass, while indirect measurements are carried out by analyzing the accuracy and accuracy of the digital calorimeter experimental set. The sensors used are thermocouple sensors and Load Cell sensors. The percentage of accuracy of the temperature reading is 99.38% with a percentage error of 0.62%. At a temperature measurement of 30 ⁰C the percentage of accuracy was 99.57%. At a temperature measurement of 70 ° C, the percentage of measurement accuracy is 99.75%. At measuring 100⁰C, the percentage of measurement accuracy was 99.82%. The accuracy percentage of the mass reading is 99.46% with a percentage error of 0.54%. In the repeated measurements of the mass of the copper cube which has a mass of 59.6 grams, the percentage of measurement accuracy is 99.60%.